KOMPOSISI BAHAN AJAR KONSEP ANALISIS REAL â€SUPREMUM DAN INFIMUMâ€ LAPISAN DALAM BUMI MELALUI PEMBELAJARAN ETNOMATEMATIKA SUNDA - Supriadi, Supriadi (Sainstek : Jurnal Sains dan Teknologi, 2017)
Teaching materials have been prepared using the concept of Ethnomatematics Sunda who believe that mathematics is a product of a culture. Supremum and Infrimum is part of mathematics that we can serve to connect the values of philosophy of Sundanese culture as a giver of value in understanding the concept of real analysis. Learning will be more memorable for studying mathematics at once understand the cultural aspects.